Variation in Prolactin Is Related to Variation in Sexual Behavior and Contact Affiliation - Snowdon, Charles T (PLoS One, 2015)
Prolactin is associated with both maternal and paternal care and appears important in developing a bond between parent and infant. In contrast with oxytocin, another hormone important in infant care, there is scant information on the role of prolactin in maintaining adult heterosexual relationships. We present here the first results demonstrating a relationship between prolactin levels and sexual and contact affiliation behavior in a pair-bonded species. We studied cotton-top tamarins, a socially-monogamous, cooperatively-breeding primate. We measured chronic urinary prolactin levels over a four week period to include the entire female ovulatory cycle and correlated prolactin levels in males and females with simultaneous measures of contact affiliation and sexual behavior. Current mothers who were no longer nursing displayed lower amounts of sexual behavior and proximity than non-breeding females and also had marginally lower levels of prolactin. The prolactin levels of males and females were similar within pairs, and variation in prolactin levels for both sexes was explained both by the amount of sexual behavior and contact affiliation. The results parallel a previous study that compared oxytocin levels with sociosexual behavior in the same species, and supports the hypothesis that both prolactin and oxytocin are involved in pair-bonding as well as in infant care.